Metal‐Coordinated Supramolecular Self‐Assemblies for Cancer Theranostics. Issue 16 (18th June 2021) - Xu, Jiating; Wang, Jun; Ye, Jin; Jiao, Jiao; Liu, Zhiguo; Zhao, Chunjian; Li, Bin; Fu, Yujie
Abstract: Metal‐coordinated supramolecular nanoassemblies have recently attracted extensive attention as materials for cancer theranostics. Owing to their unique physicochemical properties, metal‐coordinated supramolecular self‐assemblies can bridge the boundary between traditional inorganic and organic materials. By tailoring the structural components of the metal ions and binding ligands, numerous multifunctional theranostic nanomedicines can be constructed. Metal‐coordinated supramolecular nanoassemblies can modulate the tumor microenvironment (TME), thus facilitating the development of TME‐responsive nanomedicines. More importantly, TME‐responsive organic–inorganic hybrid nanomaterials can be constructed in vivo by exploiting the metal‐coordinated self‐assembly of a variety of functional ligands, which is a promising strategy for enhancing the tumor accumulation of theranostic molecules. In this review, recent advancements in the design and fabrication of metal‐coordinated supramolecular nanomedicines for cancer theranostics are highlighted. These supramolecular compounds are classified according to the order in which the coordinated metal ions appear in the periodic table. Furthermore, the prospects and challenges of metal‐coordinated supramolecular self‐assemblies for both technical advances and clinical translation are discussed. In particular, the superiority of TME‐responsive nanomedicines for in vivo coordinated self‐assembly is elaborated, with an emphasis on strategies that enhance the accumulation of functional components in tumors for an ideal theranostic outcome. Abstract : This review summarizes the recent progress made on metal‐coordinated supramolecular nanomedicines for cancer theranostic by classifying the coordination metal ions in the order of periodic table. Especially, the superiority of the tumor‐responsive nanomedicines for in vivo coordinated self‐assembling cancer theranostic is discussed, with an emphasis on how to realize high nanomedicine accumulation on tumor and therefore ideal theranostic outcome.